Making the Marvelous : Marie-Catherine d'Aulnoy, Henriette-Julie de Murat, and the Literary Representation of the Decorative Arts - Bloom, Rori, 1971- (Book collections on Project MUSE., 2022)
"At a moment when France was coming to new prominence in the production of furniture and fashion, the fairy tales of Marie-Catherine d'Aulnoy (1652-1705) and Henriette-Julie de Murat (1670-1716) gave pride of place to richly detailed descriptions of palaces, gardens, clothing, and toys. Through close readings of these authors' descriptive prose, Rori Bloom shows how these practitioners of a supposedly minor genre made a major contribution as chroniclers and critics of the decorative arts in Old Regime France. Identifying these authors' embrace of the pretty and the playful as a response to a frequent critique of fairy tales as childish and feminine, Making the Marvelous demonstrates their integration of artisan's work, child's play, and the lady's toilette into a complex vision of creativity. D'Aulnoy and Murat changed the stakes of the fairy tale, Bloom argues: instead of inviting their readers to marvel at the magic that changes rags to riches, they enjoined them to acknowledge the skill that transforms raw materials into beautiful works of art. "--